Finite Element Analysis to Determine the Optimum Stiffener Spacing on Barge Deck with 5-15-5 Sandwich Plates - Arianto, Pratama Yuli; Zharo, Risalah Alifatus; Puspita, Hery Indria Dwi; Kadhafi, Muammar; Syafiuddin, Syafiuddin (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The application of sandwich plates in marine structures provides a lightweight yet strong alternative to conventional steel plates. This study investigates the extent to which stiffener spacing on barge decks can be increased when using 5–15–5 mm sandwich plates, without exceeding the allowable stress limit. The analysis was conducted using the finite element method (FEM) in ANSYS Student R2 2024. The stiffener spacing configurations examined were 610 mm (32 stiffeners), 762 mm (24 stiffeners), 1016 mm (16 stiffeners), 1524 mm (8 stiffeners), and a model without stiffeners. The simulation results indicate that all models with stiffeners, up to a spacing of 1524 mm, satisfy the allowable stress limit of 175 MPa specified by Lloyd’s Register. In contrast, the model without stiffeners exceeds this limit and is therefore considered unsafe. Deformation analysis further shows that the maximum deflection tends to occur on the port side, particularly in regions not supported by beams or girders. As the stiffener spacing increases, the magnitude of deformation also increases, and its location shifts due to edge effects and asymmetrical support conditions. In addition, the use of sandwich plates leads to a substantial reduction in structural weight compared with conventional steel construction, ranging from 23.13% to 32.83%, depending on the stiffener spacing. Based on these results, a stiffener spacing of up to 1524 mm is considered optimal for maintaining structural safety while achieving significant weight reduction.